Socioeconomic Determinants of Climate Change Adaptation in Rice Farming: Evidence from OPLAH Areas in West Kalimantan - Nugraha, Aditya; Komariyati, Komariyati; Kurniady, Dedy (Jurnal Sosial Ekonomi Pertanian, 2026)
This study explores how socioeconomic characteristics shape climate change adaptation strategies among rice farmers cultivating OPLAH land in West Kalimantan using a quantitative explanatory survey of 95 households analyzed through descriptive statistics and cross-tabulations. Results indicate that farmers are predominantly of productive age, have primary to secondary education, extensive farming experience, moderate dependency ratios, and middle-level incomes—conditions that generally support adaptive capacity. The most widely implemented adaptation strategies incorporate flood-tolerant rice varieties, context-specific cultivation practices for flood-drought conditions, and fertilizer management aligned with recommended guidelines, while adoption of improved water management systems remains limited. Cross-tabulations indicate that higher education, longer farming experience, greater family labor, and higher incomes are consistently associated with greater implementation of climate adaptation technologies, while older, less educated, and poorer farmers lag behind. The coexistence of relatively high adoption rates of varietal and agronomic adaptations alongside low adoption of water management practices suggests that capital intensity, collective action requirements, and institutional support are critical barriers. Policies should prioritize integrated interventions that simultaneously strengthen tertiary irrigation and drainage on farmland within the OPLAH scheme, target extension and subsidies for flood-resistant varieties and climate-smart agronomy to vulnerable groups, and encourage farmer organizations to reduce coordination and investment constraints in swamp-based rice systems.